The Dynamics of Government Fiscal Policy Post COVID-19 Pandemic in Indonesia (Legal Analysis of Government Regulation instead of Law Number 1 Year 2020) - Giri, Ni Putu Niti Suari; Yusa, I Gede; Sumerthayasa, Putu Gede Arya; Kelly, Danial; Ivory, Jared (LAW REFORM, 2024)
The COVID-19 pandemic had a significant impact on various countries, including Indonesia, in particular on the securing of the state budget and state financial stability in anticipation of the systemic and comprehensive impact of the pandemic. This deviation is not in line with the Indonesian constitution, welfare state principles, and even regulations based on the principles of good legislation. This article will examine three aspects of the problem: firstly, the formation of Government Regulation Number 1 of 2020 (Perppu) concerning State Financial Policy and Stability under COVID-19 countermeasures by the formation mechanism; secondly, the constitutionality issue in the drafting of Perppu; and thirdly, the legal issue of Article 27 on the immunity of officials who carry out financial policies. This paper employs a combination of normative legal research methods, including a statutory approach, a legal conceptual approach, a legal fact approach, and a relevant case law approach. The result of the research is  that Perppu is a policy in an emergency period that contains a policy of relaxation of the implementation of the APBN is constitutional. The form of deviation that appears from Perppu is that this Perppu implements financial relaxation or sets state financial policies without involving the DPR. This has been constitutionally confirmed by Article 12 of the 1945 Constitution that the government and the DPR must determine state financial policies together. Although the constitutionality of Perppu in terms of fiscal policy is not in question, the provisions of Article 27 of Perppu that are unconstitutional can be cancelled by the Constitutional Court. The legality of Perppu relating to immunity must be implemented by prioritising the principle of good faith in carrying out the duties and functions of each state financial stakeholder during the emergency period.